2021
DOI: 10.1002/mame.202100702
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight, Abrasion‐Resistant Polybutadiene Rubber/Styrene Butadiene Rubber Foam Prepared by Three‐Step Process for Footwear Outsole Applications

Abstract: Herein, a developed microcellular foam from polybutadiene rubber (BR) and styrene butadiene rubber (SBR), which is prepared by prevulcanization, supercritical foaming, and secondary vulcanization processes is reported. It has excellent abrasion resistance and with low density. The foaming process is successfully achieved with the assistance of eco‐friendly supercritical nitrogen (sc‐N2). The microstructural analysis of BR/SBR foams indicates that the cell structure of BR/SBR foams has an obvious effect with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Volume loss is also increased upon adding more PSR, as the rubber becomes softer and the resistance deteriorates. Although the abrasion resistance of these reclaimed rubbers is lower than that of their industrial products (50–200 mm 3 ), 43–45 they are still able to withstand external force. As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Volume loss is also increased upon adding more PSR, as the rubber becomes softer and the resistance deteriorates. Although the abrasion resistance of these reclaimed rubbers is lower than that of their industrial products (50–200 mm 3 ), 43–45 they are still able to withstand external force. As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Abrasion wearability determines the product’s life and is defined by the hardness of the material, which is related to its density. Meanwhile, the thickness of the sole enhances its durability over time and was considered one of the most essential quality assessment requirements for footwear [ 15 , 16 , 25 ]. The DIN and NBS abrasion resistances of the LW 3DP 3-, 4-, and 6-PS outsoles with varied thicknesses were investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the outsole is made of various materials and tread patterns, which were decided on depending on the shoe’s purpose. There has been much interest in polymer because of its ultralight density, resilience, shock absorption, and toughness properties; it plays a significant role in versatile applications, especially in applications concerning footwear material, such as thermoplastic polyurethane (TPU), ethylene vinyl acetate (EVA), thermoplastic amide elastomer (TPAE), tyrene-(ethylene-cobutylene)-styrene polymers, and rubber material; these have been widely utilized in outsoles for safety reasons [ 25 ]. As is known, the lack of friction between the flooring and footwear could cause danger of slipping and falling, which is associated with a coefficient of friction and wear abrasion in the outsole.…”
Section: Introductionmentioning
confidence: 99%
“…24 General-purpose rubbers, such as styrene-butadiene rubber (SBR), natural rubber (NR), 1,4-cis polybutadiene rubber (BR), and polyisoprene (IR), are widely used for fabricating rubber foam their low cost and excellent mechanical properties, particularly resistance to abrasion. 25 Lemert et al investigated the swelling of IR in ScCO 2 and observed a linear relationship between swelling degree and pressure by extrapolating data from a series of styrene-isoprene copolymers. 26 Kojima et al further examined the swelling process by measuring the size change of crosslinked IR spheres and found that the swelling degree was nonlinear and seemed to be correlated with the density of CO 2 .…”
Section: Highlightsmentioning
confidence: 99%
“…Lainé et al determined the swelling and shrinking coefficients of a fluoroelastomer O‐ring in subcritical CO 2 and found that pressure changes had minimal effect on the swelling ratio, while temperature exhibited a significant influence 24 . General‐purpose rubbers, such as styrene‐butadiene rubber (SBR), natural rubber (NR), 1,4‐cis polybutadiene rubber (BR), and polyisoprene (IR), are widely used for fabricating rubber foam their low cost and excellent mechanical properties, particularly resistance to abrasion 25 . Lemert et al investigated the swelling of IR in ScCO 2 and observed a linear relationship between swelling degree and pressure by extrapolating data from a series of styrene‐isoprene copolymers 26 .…”
Section: Introductionmentioning
confidence: 99%